The timing of solid introduction in an 'obesogenic' environment: a narrative review of the evidence and methodological issues - Lynne Daniels; Kimberley M. Mallan; Alison Fildes; Jacinda Wilson (Elsevier, 2015)
Abstract Objective: To evaluate the evidence for association between obesity risk outcomes >12 months of age and timing of solid introduction in healthy term infants in developed countries, the large majority of whom are not exclusively breastfed to six months of age. Methods: Studies included were published 1990 to March 2013. Results: Twenty‐six papers with weight status or obesity prevalence outcomes were identified. Studies were predominantly cohort design, most with important methodological limitations. Ten studies reported a positive association. Of these, only two were large, good‐quality studies and both examined the outcome of early (<4 months) introduction of solids. None of the four good‐quality studies that directly evaluated current guidelines provided evidence of any clinically relevant protective effect of solid introduction from 4-5 versus ≥6 months of age. Conclusion: The introduction of solids prior to 4 months of age may result in increased risk of childhood obesity but there is little evidence of adverse weight status outcomes associated with introducing solids at 4-6 rather than at six months. Implications: More and better quality evidence is required to inform guidelines on the 'when, what and how' of complementary feeding.